2018
DOI: 10.1155/2018/8546357
|View full text |Cite
|
Sign up to set email alerts
|

An Herbal Medicine, Yukgunja‐Tang is more Effective in a Type of Functional Dyspepsia Categorized by Facial Shape Diagnosis: A Placebo‐Controlled, Double‐Blind, Randomized Trial

Abstract: Introduction Functional dyspepsia (FD) is a functional gastrointestinal disorder characterized by persistent upper dyspeptic symptoms without organic lesions. There is no standard therapy for FD. Yukgunja-tang (YGJT) is an herbal medicine used for treating upper gastrointestinal symptoms in Asia. Studies on the effect of YGJT on FD have been conducted. However, the results were inconsistent. In Hyungsang medicine, traditional Korean medicine, FD patients are classified into bladder body (BB) or gallbladder bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Choi et al, 2015; Y. Choi, Kim, Noh, Lee, & Lee, 2020; Dabos et al, 2010; Du, Ming, Chen, & Li, 2014; Eftekharafzali, Zahedi, Mehrabani, Ahmadi, & Tajadini, 2018; Fani et al, 2010; Ghoshegir et al, 2015; Giacosa et al, 2015; Holtmann et al, 2003; Jung et al, 2016; Khonche, Huseini, Mohtashami, Nabati, & Kianbakht, 2017; J. B. Kim et al, 2014; Ko et al, 2018; Li, Yang, & Li, 2013; Lin, Cai, & Xu, 1998; Liu, Piao, & Guo, 2013; Lv et al, 2017; Madisch, Heydenreich, Wieland, Hufnagel, & Hotz, 1999; Madisch, Holtmann, Mayr, Vinson, & Hotz, 2004; Mala, Thomas, Syam, Maliakel, & Krishnakumar, 2018; Masuy et al, 2020; May, Köhler, & Schneider, 2000; Mohtashami et al, 2015; C. H. Park, Kim, & Lee, 2014; J.‐W. Park et al, 2013; Pasalar et al, 2015a, 2015b; Rafieian‐Kopaei & Hosseini‐Asl, 2015; Raveendra et al, 2012; Rich et al, 2017; Ritter, Schatton, Gessner, & Willems, 1993; Rösch, Vinson, & Sassin, 2002; Su et al, 2018; Suzuki et al, 2014; Tatsuta & Iishi, 1993; Tominaga et al, 2018; Von Arnim, Peitz, Vinson, Gundermann, & Malfertheiner, 2007; Wang, Chen, & Jiang, 2017; Wen et al, 2020; Xiao et al, 2019; Zhang et al, 2013; Zhao & Gan, 2005; L. Zhao et al, 2013) were entered into meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al, 2015; Y. Choi, Kim, Noh, Lee, & Lee, 2020; Dabos et al, 2010; Du, Ming, Chen, & Li, 2014; Eftekharafzali, Zahedi, Mehrabani, Ahmadi, & Tajadini, 2018; Fani et al, 2010; Ghoshegir et al, 2015; Giacosa et al, 2015; Holtmann et al, 2003; Jung et al, 2016; Khonche, Huseini, Mohtashami, Nabati, & Kianbakht, 2017; J. B. Kim et al, 2014; Ko et al, 2018; Li, Yang, & Li, 2013; Lin, Cai, & Xu, 1998; Liu, Piao, & Guo, 2013; Lv et al, 2017; Madisch, Heydenreich, Wieland, Hufnagel, & Hotz, 1999; Madisch, Holtmann, Mayr, Vinson, & Hotz, 2004; Mala, Thomas, Syam, Maliakel, & Krishnakumar, 2018; Masuy et al, 2020; May, Köhler, & Schneider, 2000; Mohtashami et al, 2015; C. H. Park, Kim, & Lee, 2014; J.‐W. Park et al, 2013; Pasalar et al, 2015a, 2015b; Rafieian‐Kopaei & Hosseini‐Asl, 2015; Raveendra et al, 2012; Rich et al, 2017; Ritter, Schatton, Gessner, & Willems, 1993; Rösch, Vinson, & Sassin, 2002; Su et al, 2018; Suzuki et al, 2014; Tatsuta & Iishi, 1993; Tominaga et al, 2018; Von Arnim, Peitz, Vinson, Gundermann, & Malfertheiner, 2007; Wang, Chen, & Jiang, 2017; Wen et al, 2020; Xiao et al, 2019; Zhang et al, 2013; Zhao & Gan, 2005; L. Zhao et al, 2013) were entered into meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The overall score was calculated by adding points for each item, with higher scores indicating more severe indigestion symptoms. The TDS questionnaire has been used as the primary outcome measure in several clinical trials on FD (Zhang et al, 2013;Ko et al, 2018). It was evaluated throughout the 4 weeks study period, including at follow-up visits.…”
Section: Primary Outcome Measurementioning
confidence: 99%
“…YGT consists of Atractylodis lanceae rhizoma (5.63 g), Ginseng radix (3.75 g), Pinellia tubers (5.63 g), Poria cocos (3.75 g), Zizyphi fructus (3.75 g), Aurantii nobilis pericarpium (3.75 g), Glycyrrhizae radix (1.88 g), and Zingiberis rhizoma (3.75 g). Several studies using YGT reported the positive effect on functional gastrointestinal diseases 8,10 , however, there are still lack of studies on the use of YGT for IBS.…”
Section: ⅰ Introductionmentioning
confidence: 99%